Letters sent by the assistant secretaries of agriculture, 1889-1919 - Willits, Mr. (Edwin), 1830-1896; Dabney, Charles William, 1855-1945; Brigham, Joseph H.; Hays, W. M. (Willet Martin), 1859-1916; Galloway, B. T., 1863-1938; Vrooman, Carl Schurz, 1872-1966 (National Archives microfilm publications., 1947)
Correspondence of Assistant Secretaries of Agriculture Edwin Willits (Mar. 23, 1889-Dec. 31, 1893), Charles W. Dabney, Jr. (Jan. 1, 1894-Mar. 22, 1897), Joseph H. Brigham (Mar. 23, 1897-June 29, 1904), Willet M. Hays (Dec. 21, 1904-Mar. 7, 1913), Beverly T. Galloway (Mar. 17, 1913-July 31, 1914) and Carl S. Vrooman (Aug. 17, 1914-Dec. 31, 1918)